Brand Attitude, Purchase Intention, and Sustainable Clothing: Moderating Role of Brand Luxury and Consumer Experience - Ken Kumagai; Shin’ya Nagasawa (New Innovations in Economics, Business and Management Vol. 9, 2022)
Plastic waste is a serious social issue relevant to every company, regardless of the level of brand luxury. Accordingly, fashion companies are attempting to develop sustainable apparel made from post-consumer plastic bottles. However, previous studies have not examined the effect of this sustainable product type on consumer behavior, whereas comprehensive sustainable development has been extensively discussed in luxury branding research. As a result, the purpose of this research is to see how the introduction of sustainable plastic clothing influences consumer brand attitudes and purchase intentions. We collected 440 samples via an online survey in Japan and conducted moderated mediation analyses; the results showed that the launch of sustainable plastic clothing affects brand attitude positively, influencing purchase intention both directly and indirectly. Additionally, brand luxury and brand experience allegedly weaken the effect of this sustainable product launch, whereas the influence of sustainable product experience is insignificant. Luxury brands should restructure their current marketing to promote sustainable items more effectively and adjust their branding techniques to match with sustainability in order to successfully launch this type of sustainable fashion. Otherwise, their brand elegance may be a liability, as plastic recycling is becoming more and more of a social necessity.